ANALISIS EKSTERNAL DAN INTERNAL DALAM MENENTUKAN NON PERFORMING FINANCING BANK UMUM SYARIAH DI INDONESIA - Mutamimah Mutamimah; Siti Nur Zaidah Chasanah (Jurnal Bisnis dan Ekonomi, 2012)
This study aims to examine and analyze the Non Performing Financing of Sharia Banks in Indonesia. Thisresearch is important to do because of bad credit has a very high fluctuation. As for some of the factorsanalyzed in the influence of Non Performing Financing is: Gross Domestic Product, Inflation, Exchange Rates,policy type of financing Islamic banks as well as the allocation ratio murabaha receivables rather than theallocation of profit loss sharing financing (RF).The population in this study were all Islamic Banks in Indonesia.The sampling technique used was purposive sampling, which is a sampling method based on multiple criteria,namely: a). Islamic Banks which publish quarterly financial statements during the period 2005-2011. b). IslamicCommercial Bank which has a complete data based on the variables studied. Data analysis methods used in thisstudy is an analysis of Multiple Linear Regression. These results indicated that the growth of real GDP and theexchange rate of rupiah against the dollar had a positive impact on the Non-Performing Financing but notsignificant; inflation has a negative impact to Non Performing Financing and significant; profit and loss sharingratio of return on total return of financing (RR ) has a negative effect on the Non-Performing Financing, but notsignificant. Murabaha financing allocation ratio to the allocation of profit loss sharing financing and asignificant negative effect on Non Performing Financing.Key words: non performing financing, GDP, kurs, inflation, total return to financing.